Tinidazole versus Ornidazole in Amebic Dysentery in Children (a double blind trial) - Amer Panggabean; Adi Sutjipto; Dachrul Aldy; A. H. Sutanto; Helena Siregar (Indonesian Pediatric Society, 1980)
Between January and June 1978, a double blind trial was conducted in 3.5 children, suffering from Amebic Dysentery in the OPD of the General Hospital Medan. The children were treated ambulatory, either with Tinidazole or Ornidazole, with a dose of 50 mg/kg body weight/day for 3 consecutive days, under close supervision. All the children, except on in the Tinidazole group (case no. 20), gave excellent responses. Disappearance of ameba's blood and mucus from the stools occurred in all of the patients after 2 days of treatment. There was no significant difference in the results of treatment with Tinidazole and Ornidazole (p>0.05). Side effects were minimal. Marked vomiting occurred in one patirnt of the Ornidazole group.